SANKSI PIDANA ANAK TERHADAP PENYALAHGUNAAN NAPZA DIKAJI DARI LEGAL JUSTICE - Rajasa, Alvien Okta; Kristiyadi, Kristiyadi (Verstek, 2022)
Narcotics are drugs used for the medical world for patients who have certain diseases. Of course, with the rules of use according to the instructions of the doctor concerned. However, the problem of drug abuse has become a national and international problem. Narcotics abuse can cause physical, mental, psychological, emotional and attitudinal damage in society. Children who are involved in drugs must get protection both psychologically and legally to avoid psychological disorders that may occur in children and preventive measures of stigmatization of children in conflict with the law and it is hoped that children can return to the social environment in society. The purpose of the research is an objective objective, namely to determine the suitability of the judge's assessment of the evidence in decision number 001/pid.sus-anak/2021/pn skt with the provisions of the Criminal Procedure Code and Law Number 35 of 2009 concerning Narcotics. Meanwhile, the subjective goal is to add, broaden the author's horizons and abilities in studying problems in the field of Criminal Procedure Law. The benefits of research consist of theoretical benefits and practical benefits. The theoretical benefits of the research results can be used to explore the theories that have been obtained by the author in writing legal writing. And the practical benefit is that it can provide benefits and additional knowledge for various parties in need, especially in community groups and in general and parties related to the subject matter. Keywords: Sanctions, Child Crime, Narcotics, Legal Justice